Report of the High Level Committee on Floods Flood Control in Various River Basins Volume II - Planning Commission (Planning Commission, 1958)
In Volume I of their report, submitted in December 1957,. the Committee made a general assessment of the flood problems in the country and dealt with the principles and policies to be followed in dealing with them. Also, other matters having an important bearing on flood control, such as, a review of past efforts, flood damage in various parts of the country, methods of flood control, soil conservation and organisational aspects were dealt with. In the present Volume, the Committee have dealt with the flood problems in the various river basins, and have indicated the lines on which they should be tackled.
Government of India Ministry of Irrigation and Power
Government of India Ministry of Irrigation and Power